Barnacle Epibiosis on Sea Turtles in Korea: A West Pacific Region With Low Occurrence and Intensity of Chelonibia testudinaria (Cirripedia: Chelonibiidae) - Kim, Hyun Kyong; Chan, Benny K. K.; Yi, Changho; Kim, Il-Hun; Choi, Yu Na (Frontiers in Ecology and Evolution, 2022)
Loggerhead and green sea turtles are common in the world’s major oceans. External surfaces of sea turtles are often colonized by epibiotic chelonibiid barnacles. Barnacle taxonomy studies in Korea began in 1985 but until present, no turtle barnacles were recorded. This suggests the diversity and frequency of occurrence of turtle barnacles in Korean waters are low, or turtle barnacles have been under-studied. The present study based on six years of sea turtle stranding records in Korea (2015–2020) examined the diversity, frequency and intensity of turtle barnacle occurrence. Of the 55 recorded strandings, loggerhead sea turtles were most common (58%), followed by green sea turtles (33%). Only one species of barnacle, Chelonibia testudinaria, was found on loggerhead and green sea turtles. The average frequency of barnacle occurrence on green sea turtles was 28%, with intensity 2.42±2.7 barnacles per turtle. 11% of green sea turtles had barnacles, with a mean density of one individual per turtle. Frequency of barnacle occurrence and intensity on green sea turtles appears five times lower than the green sea turtle populations in Okinawan, Bornean and Australian waters in the Indo-Pacific. It is possible that turtle barnacle larval pools in cold, high latitude Korean waters are lower than adjacent and other locations in the Indo-Pacific.Frequency of barnacle occurrence and intensity on loggerhead sea turtles in Korea falls within the range in other Indo-Pacific locations.Longer migratory behavior of loggerhead sea turtles may allow them to pass through different larval pools in the Indo-Pacific waters and gain higher barnacle abundances.